Dampak Penggunaan Obat Off Label Terhadap Adverse Drug Reactions (ADR): Studi Pada Pasien Pediatri - Nur Hidayah, Fitri; Iqbal, Muhamad; Wardana, Muhammad Fitra; Triyandi, Ramadhan (Medula, 2024)
Limited types of drugs that can be used in the age range of children aged 0-2 years have resulted in treatment of patients using off-label drugs. Unwanted drug reactions (ROTD) are a health problem in society that occurs especially in the pediatric population. ROTD in children can have relatively more severe effects when compared to adults. Research on off-label drug use has been carried out in several places in Indonesia but most of it is limited to the percentage of off-label drug use and it is also not known further about its influence on the emergence of ROTD, namely information on drug labeling, efficacy and safety in the pediatric population is limited. Limited information results in many off-label drug prescribing in pediatric patients. Several studies aim to obtain an overview of off-label drug use in pediatric patients. A review of this literature is that off-label drug use in pediatric patients is still an issue that needs attention. With a better understanding of off-label drug use, steps can be taken to improve the safety and effectiveness of treatment in pediatric patients.